2014
DOI: 10.1098/rstb.2013.0517
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-8 promotes robust motor axon targeting by coordinate regulation of cell adhesion molecules during synapse development

Abstract: Neuronal connectivity and specificity rely upon precise coordinated deployment of multiple cell-surface and secreted molecules. MicroRNAs have tremendous potential for shaping neural circuitry by fine-tuning the spatio-temporal expression of key synaptic effector molecules. The highly conserved microRNA miR-8 is required during late stages of neuromuscular synapse development in Drosophila. However, its role in initial synapse formation was previously unknown. Detailed analysis of synaptogenesis in this system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…We have shown that the miR-17-92 cluster within distal axons of cortical neurons locally promotes axonal growth by targeting PTEN/mTOR signals [16]. Others also demonstrate that miR-338[59], miR-132[13], miR-9 [60], miR-8[61] are enriched in distal axons and regulate their target genes involving energy metabolism and cytoskeleton function leading to modulating axonal growth. Distal axons contain miRNA machinery proteins [60,59,16,13].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the miR-17-92 cluster within distal axons of cortical neurons locally promotes axonal growth by targeting PTEN/mTOR signals [16]. Others also demonstrate that miR-338[59], miR-132[13], miR-9 [60], miR-8[61] are enriched in distal axons and regulate their target genes involving energy metabolism and cytoskeleton function leading to modulating axonal growth. Distal axons contain miRNA machinery proteins [60,59,16,13].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these miRNAs also exhibited overlapping cellular functions, contributing to processes such as tumorigenesis [23][24][25][26][27][28][29][30], differentiation [31][32][33], proliferation [34][35][36][37][38], apoptosis [39][40][41][42], and cell cycle regulation [34,43,44]. A subset of the miRNAs was associated with nervous system-specific processes, such as differentiation [45][46][47][48][49], lifespan [50], neurite guidance [51][52][53], or synaptogenesis [54][55][56]. We were specifically interested in miRNAs known to contribute to neuronal differentiation and/or axonal guidance, processes that are known to be regulated by RA [10,57].…”
Section: Identification Of Mirnas That Were Differentially Regulated mentioning
confidence: 99%
“…miR-21 and miR-222 promote neurite outgrowth by targeting Sprouty2 and PTEN, respectively [40,41]. miR-8, miR-431, miR-145, and miR-138 have been shown to play regulatory roles in neurite outgrowth [42][43][44]46]. In addition, lncRNA-uc.217 regulates neurite outgrowth in DRG neurons following peripheral nerve injury [45].…”
Section: Neuronal Cellsmentioning
confidence: 98%
“…Neural stem/progenitor cells Promote proliferation miR-25 [12]; miR-137 [13]; miR-184 [14]; miR-195 [15] Induce differentiation miR-9, siRNA-TLX [16]; let-7d [17]; miR-137 [13]; miR-184 [14]; miR-195 [15]; miR-34a [18]; lncRNA-BDNF-AS, siRNA-BDNF-AS [19] Mesenchymal stem cells Induce differentiation miR-9 [20]; miR-124 [21] Reduce differentiation miR-128 [22] Neuronal cells Inhibit cell death miR-223 [23]; miR-181c [24]; miR-592 [25]; miR-424 [26]; miR-23a-3p [27]; miR-23a/b, miR-27a/b, siRNA-Apaf-1 [28] Promote cell death miR-134 [29]; miR-200c [30]; miR-30a/b [31][32][33]; miR-124 [34]; miR-711 [35] Regulate degeneration and apoptosis miR-20a [36]; miR-29b [37]; miR-146a, siRNA-miR146a [38] Promote neurite outgrowth miR-7 [39]; miR-21 [40]; miR-222, siRNA-PTEN [41]; miR-8 [42]; miR-431 [43]; miR-145 [44]; lncRNA-uc.217 [45]; miR-138, siRNA-SIRT1 [46] Microglial cells Inhibit inflammation let-7c [47]; miR-124, siRNA-C/EBP-α [48] Promote pro-inflammation miR-155 [49] Inhibit activation let-7c-5p [50] Astrocytes P...…”
Section: Nervementioning
confidence: 99%